PENGARUH KUALITAS PRODUK TERHADAP NIAT MEMBELI ULANG PRODUK WHITELAB SKINCARE - Aulia Putri Ramalah; Agus Hasan Pura Anggawidjaja (Universitas Katolik Parahyangan, 2025)
The growth of the beauty business sector has driven the emergence of various new companies, one of which is Whitelab, established in 2020 and producing a range of skincare products. This study aims to examine the effect of product quality on consumers repurchase intention of Whitelab skincare products. The research employed a quantitative method with data collected through questionnaires and literature review. The study involved 100 respondents who had purchased and used Whitelab products within the past six months, using purposive sampling techniques. The results indicate that product quality has a significant influence on consumers repurchase intention, contributing 72.9%. These findings highlight that product quality is a crucial factor for companies to consider in order to enhance customer loyalty and maintain competitiveness amid the intense rivalry in the skincare industry.